ANALYSE SÉMANTIQUE ET IDÉOLOGIQUE DE LA MATERNITÉ EN PAYS BAOULÉ-DOHOUN (CÔTE D’IVOIRE) - Dieu-Donné, Kouadio M’bra Kouakou (European Scientific Journal, ESJ, 2015)
To the BaoulÃ©-Dohoun of BendÃ¨kouassikro (municipality of BouakÃ©), the motherhood represents a field symbolic system of the social life. Humans as well as supranaturals (spirits, geniuses, etc.) play a leading role. This consideration of the global environment places the women and the girls at the heart of the genesic process : they are â€œfightersâ€ for the survival of the humanity. They donâ€™t thus hesitate to risk their life for their survival and that of their children. They are subjected (submitted) to rites such as juvenile rite or rite of wash of the girl â€œblahunzilÃ¨â€. The semantic and lexical fields indicate the interest of the obstetric route and the social representations of the motherhood in BaoulÃ©-Dohoun country.